Specific VpU codon changes were significantly associated with gp120 V3 tropic signatures in HIV-1 B-subtype - Dimonte, Salvatore (Virol Sin, 2012)
After infection and integration steps, HIV-1 transcriptions increase sharply and singly-spliced mRNAs are produced. These encode Env (gp120 and gp41) and auxiliary proteins Vif, Vpr and VpU. The same localization within the unique structure of the mRNAs suggests that the VpU sequence prior to the Env could affect the Env polyprotein expression.The HIV-1 infection process begins when the gp120 subunit of the envelope glycoprotein complex interacts with its receptor(s) on the target cell. The V3 domain of gp120 is the major determinant of cellular co-receptor binding. According to phenotypic information of HIV-1 isolates, sequences from the VpU to V3 regions (119 in R5- and 120 X4-tropic viruses; one per patient) were analysed. The binomial correlation phi coefficient was used to assess covariation among VpU and gp120(V3) signatures. Subsequently, average linkage hierarchical agglomerative clustering was performed. Beyond the classical V3 signatures (R5-viruses: S11, E25D; X4-viruses: S11KR, E25KRQ), other specific V3 and novel VpU signatures were found to be statistically associated with co-receptor usage. Several statistically significant associations between V3 and VpU mutations were also observed. The dendrogram showed two distinct large clusters: one associated with R5-tropic sequences (bootstrap=0.94), involving: (a) H13NP(V3), E25D(V3), S11(V3), T22A(V3) and Q61H(VpU), (b) E25A(V3) and L12F(VpU), (c) D44E(VpU), R18Q(V3) and D80N(VpU); and another associated with X4-tropic sequences (bootstrap=0.97), involving: (i) E25I(V3) and V10A(VpU), (ii) 0-1insV(VpU), H13R(V3), I46L(VpU), I30M(V3) and 60-62del(VpU), (iii) S11KR(V3) and E25KRQ(V3). Some of these pairs of mutations were encoded always by one specific codon. These data indicate the possible VpU mutational patterns contributing to regulation of HIV-1 tropism.